(untitled) (Scientific journal of the Fergana State University, 2023)
The purpose of this article is to reveal the phenomenon of phraseological transformation by highlighting the structural-semantic structure of lexical phraseologisms of the Uzbek language, their syntagmatic implementation in the speech environment.It uses scientific methods such as description, comparison, classification, modelling and differential-semantic.The questions of determining the ways of formation types - expansion, contraction, exchange and mixed type of derivative units, in particular transformants formed as a result of changes in phraseological phrases of the Uzbek language in the speech environment, and their modelling are analysed.